30. Nesset Kobbenesset: Samisk smie brukt i middelalder og nyere tid - Figenschau, Ingar Olsborg; Bruun, Inga Malene (Tromura, 2025)
Kobbenesset was recorded as a turf hut (gammetuft) in 2015. The archaeological investigation in 2021 uncovered a forge with a centrally placed hearth. Finds included slag, scale, slag spheres, anvil stones, and whetstones. Metallurgical analyses indicate that the forge was used for secondary smithing.